Bridging the Gap: What S&C can Learn from Sport Coaching - Harvey Anderson (International Universities Strength and Conditioning Association, 2020)
One of the ways for any discipline to develop is to look to the work, practices, knowledge bases and lessons learned from other disciplines who have trodden similar paths before us, preferable those more closely related (Lyle, 2018).